Extraction of cellulose-based polymers from textile wastes - Felgueiras, Helena Prado (2022)
[Excert] The extraction and exploration of cellulose-based polymers is an exciting area of research. For many years, wood (especially from bleached kraft wood pulp) was considered the main source of cellulosic compounds because of its abundance in nature [1,2]. However, in the past decade, researchers have been devoted to finding alternatives to extract cellulose from byproducts of agricultural crops and/or textile wastes, both highly available at a very reduced raw material cost.